Insights from physiology into myometrial function and dysfunction. Issue 12 (13th September 2015) - Wray, Susan
Abstract : New Findings: What is the topic of this review? I focus on clinical aspects of uterine physiology, specifically, myometrial contractility. I bring together and contrast findings using physiological approaches and those using newer techniques, 'omics'. What advances does it highlight? Physiological studies have recently shed light on the myometrium in twin pregnancies, but there have been no 'omic' approaches. In contrast, studies of preterm delivery using newer approaches are generating new research avenues, whereas traditional approaches have not flourished. Finally, I describe significant advances in understanding of 'slow‐to‐progress' labours, achieved using physiological and clinical approaches. Advances in molecular, genetic and 'omic' technologies are fuelling the thirst for better understanding of the uterus and application of this information to problems in pregnancy and labour. Progress has, however, been limited while we still have an incomplete understanding of some of the basic physiology of uterine smooth muscle (myometrium). In this review and opinion piece, I explore some of the fascinating findings from selected recent studies and see how these may provide new avenues for physiological and clinical research. It is also the case, however, that there is still limited mechanistic understanding about physiological and pathophysiological processes in the myometrium. This lack of understanding limits the usefulness of some findings from genomic and allied studies. By focusing on some key recent findings and relating these to two important clinical problems in childbirth that involve myometrial activity, namely preterm delivery and difficult labours, the interplay between our physiological knowledge and the information provided by newer technologies is explored. My opinion is that physiology has provided much more new mechanistic insight into difficult births and that the newer technologies may lead to breakthroughs in preterm birth research, but that this has not yet happened. Abstract :